Association between GNB3 C825T Polymorphism and Sex in Iraqi Patients with Myocardial Infarction - Ayat K. Taher (Journal of Global Pharma Technology, 2018)
Objective: The C825T polymorphism of the GNB3 gene is associated with hypertension, obesity and diabetes, while the association between the polymorphism and MI has been poorly explored. The aim of present study was to investigate the frequency distribution of C825T polymorphism of GNB3 gene in three study groups (G1, G2 and healthy controls) and its association with sex in Iraqi patients with myocardial infarction.  Methods: the study consist of 120 subjects (40 healthy individuals, 40 patients with only MI and 40 patients with MI and hypertension); genomic DNA extracted from whole blood, and C825T polymorphism was detected by polymerase chain reaction- Restriction fragment length polymorphism (PCR-RFLP). Results: the results show that most of patients were males it was (77.5 %) in G1 patients, while it was (70 %) in G2 patients, the difference was significant (P < 0.01) between males and females in both groups. the frequency of homozygous (CC) genotype G1 was (19.35 %) in males and (22.22%) in females and it was (28 %) for males, (16.67%) for females in G2. The heterozygous (CT) genotype for G1 in males and females was (61.29 %, 11.11%) respectively, for G2 it was (28 %, 16.67%) respectively. While, homozygous (TT) genotype in G1 was (19.35 %) for males and (66.67%) for females, and for G2 it was (14.29 %, 50.00%) in males, females respectively. The C allele frequency in G1 patients was (0.50) in males much higher than females (0.28), while T allele frequency was higher in females (0.72) than males (0.50). The frequency of C allele in G2 was (0.55, 0.33) for male and female respectively, and T allele frequency was (0.45) in male and it was higher in female (0.67). Odds ratio in both groups (G1and G2) was more than one according to (CT) genotype so it consider as a risk factor to MI for males while, (TT) genotypes consider as a risk factor to MI for females, while (CC) genotype can consider as a protective factor from MI since OR was more than one in both patient groups (G1 and G2). Conclusion: the polymorphism C825T of GNB3 gene in Iraqi population associated with myocardial infarction but more often in females.Keywords: Myocardial Infarction, G protein, GNB3, C825T polymorphism.